Analisis Kualitas Pelayanan Terhadap Kepuasan Jasa KRL Commuterline Menggunakan Metode Quality Function Deployment (QFD) Di Stasiun Bojonggede - Nuraini (2020)
The competition in the transportation world is getting tougher. The way for the transportation industry to continue to improve service products with comfort and quality of service to meet customer satisfaction. KRL CommuterLine is an economical transportation choice, can reach, has extensive and economical operational services. The study was conducted at Bojonggede Station. The method used to measure service quality with service quality dimensions to determine customer needs variables that are not met with Qualiity Functiion Deeployment (QFD) is by compiling a House of Qualiity (HOQ) matriix that provides benefits according to the needs of the highest quality. Referring to Duru et al, 2011 in general QFD only refers to customer satisfaction and ignores the company's own satisfaction. Therefore, in this study, a development was carried out to be able to accommodate this, namely the QFD process through the House of Quality (HOQ) from two directions, namely customer HOQ and company HOQ. The CommuterLine KRL at Bojonggede Station needs to provide friendly, safe and comfortable services for passengers in accordance with an increase in meeting the needs and expectations of customers in orrder to obtaiin an optiimal levell of service.